Implementasi Flipped Classroom Berbasis Pedagogi Ignasian dengan Integrasi AI untuk Mengembangkan 4C Mahasiswa dalam Pembelajaran Akuntansi Keuangan Lanjutan II - Brataningrum, Natalina Premastuti; Nugraheni, Benedecta Indah (Buletin Literasi Budaya Sekolah, 2025)
This study aims to design and develop a flipped classroom learning model based on Ignasian pedagogy with efective use of Gen AI to develop the 4Cs (competence, consience, compassion, and commitment) in Advance Financial Accounting II learning. The method used in this study is design-based research with three main phases, namely: (1) the preliminary design phase, and (3) the restrospective analysis phase. This study was implemented in the Advanced Financial Accounting II course in the Accounting Education Program at Sanata Dharma University, Yogyakarta, with a total of 31 course participants. The result of the study show that implementation of flipped learning based on Ignatian pedagogy utilizing AI-generated resources can develop student’ 4C skills. For the competence aspec, most students hane mastered the competencies of the Advanced Financial Accounting II course; for the conscience aspect, measuring student independence falls into high and very high categories; for the compassion aspect, measuring student collaboration is categorized as high and very high.